3x+9=6x+4

Simple and best practice solution for 3x+9=6x+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+9=6x+4 equation:


Simplifying
3x + 9 = 6x + 4

Reorder the terms:
9 + 3x = 6x + 4

Reorder the terms:
9 + 3x = 4 + 6x

Solving
9 + 3x = 4 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
9 + 3x + -6x = 4 + 6x + -6x

Combine like terms: 3x + -6x = -3x
9 + -3x = 4 + 6x + -6x

Combine like terms: 6x + -6x = 0
9 + -3x = 4 + 0
9 + -3x = 4

Add '-9' to each side of the equation.
9 + -9 + -3x = 4 + -9

Combine like terms: 9 + -9 = 0
0 + -3x = 4 + -9
-3x = 4 + -9

Combine like terms: 4 + -9 = -5
-3x = -5

Divide each side by '-3'.
x = 1.666666667

Simplifying
x = 1.666666667

See similar equations:

| x^2-36x=8140 | | 8(x-.75)+12=-10 | | 1-4n=29 | | F(x)=13x+7 | | -1x-3=-2x-4 | | 5-(8+10)=8+5 | | 10+4q=34 | | 18+-1(3-2y)=3(y-5) | | x^2-36x=5605 | | u^2-4u+4-80=0 | | 8c+8=224 | | r+at=v | | 10-9x-5=-(3x+5)-2(2x-5) | | e-(-73)=-22 | | t(-16)=9 | | -5a-7+4a=-(9-7) | | 102=-7r-3 | | t(-16)=-9 | | b=-4t^2 | | v^2+20v=0 | | .3(12x-15)=3x+9 | | y^2-8y+16=2y^2-12y-5 | | 0.4x-12=-22 | | 758+8=750 | | .25x+-0.5=15-x | | 750+8=742 | | -2x-(-4y)=1 | | 3c-5+2c= | | 6t=15 | | -10+7=x+4+4 | | -5=v/16 | | 12x^4-480x^2-4500=0 |

Equations solver categories